Paradoks Kemanfaatan dan Keadilan: Analisis Ekonomi-Politik Kebijakan Tax Amnesty Berulang di Indonesia - Riris Prasetyo; Mohammad Rezza Fahlevvi (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2025)
ABSTRACT The recurrent implementation of tax amnesty policies in Indonesia has sparked a fundamental tension between pragmatic fiscal needs and rule-of-law principles. Previous studies tend to focus on quantitative fiscal impacts while overlooking the long-term implications for legal integrity. Therefore, this research is conducted to critically deconstruct how such policies risk metamorphosing into mechanisms of legalized impunity due to the underlying political-economy structure. Employing a qualitative approach with an interdisciplinary library research design, the dialectic between fiscal expediency (Zweckm├ñ├ƒigkeit) versus justice (Gerechtigkeit) and legal certainty (Rechtssicherheit) is analyzed using Gustav Radbruch's legal philosophy framework and political-economy theories. The results indicate that recurrent amnesty is not merely a fiscal strategy, but a triumph of short-term pragmatic calculus driven by clientelism dynamics and oligarchic wealth defense. This policy has been shown to create discriminatory parity gaps, erode tax morale, and undermine legal predictability through the phenomenon of strategic non-enforcement. It is concluded that without structural reform, tax amnesty poses an existential threat to legal integrity; thus, the implementation of strict judicial